Pengaruh Harga dan Saluran Distribusi Terhadap Volume Penjualan Usaha Kerajinan Kayu di Kecamatan Ubud - Dewa Ayu Agung Saras Winda Sri Wahyuni; Kadek Rai Suwena (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2026)
This study aims to examine the influence of price and distribution channels on sales volume among woodcraft entrepreneurs in Ubud District. The research design used is quantitative causal. The sample used in this study was 83 respondents of woodcraft entrepreneurs in Ubud District using proportional random sampling technique. The instrument used in this study was a questionnaire and tested with multiple linear regression analysis. The results of this study indicate (1) Price has a positive and significant effect on sales volume. (2) Distribution channels have a positive and significant effect on sales volume. (3) Price and distribution channels simultaneously have a positive and significant effect on sales volume, with a contribution of 79.2% while 20.8% is influenced by other factors.